An intracellular anchor regulates the distribution of bioactive molecules. Issue 73 (19th August 2016) - Wang, Jianwu; Li, Shengliang; Chen, Hui; Hu, Rong; Li, Meng; Lv, Fengting; Liu, Libing; Ma, Yuguo; Wang, Shu
Abstract : A pre-targeted anchor strategy was developed to regulate the intracellular distribution of bioactive molecules in specific organelles based on bioorthogonal tetrazine ligation. Abstract : Based on bioorthogonal tetrazine ligation, a pre-targeted anchor strategy was developed to regulate the intracellular distribution of bioactive molecules. This strategy could solve the issue regarding the permeability and targeting ability of bioactive molecules in the specific organelles of living cells.